Influence of Microwave Incinerated Rice Husk Ash on Hydration of Foamed Concrete - R. Bayuaji; M. F. Nuruddin (Advances in Civil Engineering)
This research explains the results of an investigation carried out to understand the influence of a microwave incinerated rice husk ash (MIRHA) powder on foamed concrete (FC) hydration. The experimental work was designed using the Taguchi approach. This method was selected to have a target for the optimum working conditions of the parameter that affects some physical properties of concrete mixtures. The loss on ignition (LOI) method was used to establish the nonevaporable water (wn) content at all selected ages of hydration. It was observed that the MIRHA powder showed lower nonevaporable water contents than the normal FC, indicating that MIRHA powder facilitated enhancement in FC hydration. The optimum FC properties were achieved at 10% MIRHA composition as proven from the highest compressive strength. This level corresponds to the highest values in change in nonevaporable water and degree of hydration.